Cultural mediation in the performing arts: progress and resistance - Bordeaux, Marie-Christine; Santos, Ricardo [UNESP]; Fernandes, Renata [UNESP] (Univ Sao Paulo, Escola Comunicacoes & Artes, 2024)
The most diverse art audiences are becoming increasingly familiar with techniques and ways of having their encounters with different artistic experiences mediated. However, the development of mediation as a professional function is unevenly distributed between the different cultural areas. Could this imbalance signal a chronic inability to synthesize popular education and artistic and cultural policy, or does it result from an impossible synthesis between the practices and challenges of the areas of arts and culture? The analysis of mediation in theater and dance in this study provides some answers to these questions, highlighting the unique and diverse nature of art and cultural objects as opposed to a single, homogeneous view of the role of cultural mediation and the function of mediating agents.
Keywords: Cultural mediation; Mediation in the performing arts; Theater mediation; Mediation in dance